2018
DOI: 10.1111/jgs.15506
|View full text |Cite
|
Sign up to set email alerts
|

American Geriatrics Society and National Institute on Aging Bench‐to‐Bedside Conference: Sensory Impairment and Cognitive Decline in Older Adults

Abstract: This article summarizes the presentations and recommendations of the tenth annual American Geriatrics Society and National Institute on Aging Bench-to-Bedside research conference, “Sensory Impairment and Cognitive Decline,” on October 2–3, 2017, in Bethesda, Maryland. The risk of impairment in hearing, vision, and other senses increases with age, and almost 15% of individuals aged 70 and older have dementia. As the number of older adults increases, sensory and cognitive impairments will affect a growing propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
184
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 189 publications
(188 citation statements)
references
References 36 publications
2
184
0
2
Order By: Relevance
“…A recent American Geriatrics Society and National Institute on Aging Conference recommended that in future studies "data need to be stratified according to sex." 27 Therefore, we investigated the relation of self-reported hearing loss and incident subsequent SCF decline in an ongoing cohort of 20,193 women in the Nurses' Health Study.…”
Section: Introductionmentioning
confidence: 99%
“…A recent American Geriatrics Society and National Institute on Aging Conference recommended that in future studies "data need to be stratified according to sex." 27 Therefore, we investigated the relation of self-reported hearing loss and incident subsequent SCF decline in an ongoing cohort of 20,193 women in the Nurses' Health Study.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high prevalence of sensory and cognitive impairments in older adults, there are several key gaps in knowledge about the effects of this combination on outcomes, such as healthcare utilization and cost . This combination may be a potent driver of healthcare utilization and cost due to high rates of functional impairment, increased skilled nursing utilization, and increased risk for steeper cognitive decline .…”
mentioning
confidence: 99%
“…(2) Other factor(s) cause both sensory impairments and cognitive impairment. Adapted from reference . Panel B: Associations between sensorineural and cognitive functions due to close neural integration.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Several studies reported associations between sensory impairments and development of cognitive impairment or decline, [11][12][13][14][15] and we previously showed that impairments in hearing, vision, or olfaction are associated with worse cognitive function in middle-aged adults 16 and the development of cognitive impairment in older adults. 17 It was hypothesized that shared etiologic pathways may explain these associations between sensorineural aging changes and cognitive decline ("common cause" hypothesis), whereas others have suggested that sensory loss causes cognitive decline due to sensory deprivation, social isolation, or cognitive overload [18][19][20] (Figure 1A). Alternatively, these associations may reflect the close integration of neural processing in sensory systems and cognition ( Figure 1B).…”
mentioning
confidence: 99%